2019
DOI: 10.1038/s42003-019-0290-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 12 genetic loci associated with human healthspan

Abstract: Aging populations face diminishing quality of life due to increased disease and morbidity. These challenges call for longevity research to focus on understanding the pathways controlling healthspan. We use the data from the UK Biobank (UKB) cohort and observe that the risks of major chronic diseases increased exponentially and double every eight years, i.e., at a rate compatible with the Gompertz mortality law. Assuming that aging drives the acceleration in morbidity rates, we build a risk model to predict the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
117
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 72 publications
8
117
0
2
Order By: Relevance
“…Recent GWAS have changed approaches from comparisons of extremely long-lived persons with controls in the normal age range [57,58] to studies of parental lifespan [14,59,60], which allow much larger samples. And new methods are being applied to conduct GWAS of longevity processes in samples of still-living individuals [61]. The candidate genes APOE and FOXO3A are the best-studied longevity genes, and they have replicated in GWAS of multiple designs (reviewed here [62]).…”
Section: New Developments In Molecular Epidemiology Of Agingmentioning
confidence: 99%
“…Recent GWAS have changed approaches from comparisons of extremely long-lived persons with controls in the normal age range [57,58] to studies of parental lifespan [14,59,60], which allow much larger samples. And new methods are being applied to conduct GWAS of longevity processes in samples of still-living individuals [61]. The candidate genes APOE and FOXO3A are the best-studied longevity genes, and they have replicated in GWAS of multiple designs (reviewed here [62]).…”
Section: New Developments In Molecular Epidemiology Of Agingmentioning
confidence: 99%
“…In a follow-up study of over a million parental lifespans, Timmers et al 10 confirmed the association between variants in LPA and parental lifespan. Interesting results were also recently reported by Zenin et al 23 who have shown that variants in LPA may be associated with disease-free survival (also known as healthspan) in the UK Biobank, thereby suggesting that lower Lp(a) might not only be associated with longer lifespan, but also with healthy living into old age. These studies however did not investigate the potential effect of genetically-elevated Lp(a) levels on parental lifespan or healthspan using robust genetic analyses such as MR. By reporting a significant effect of high Lp(a) levels on shorter parental lifespan using MR, our study strengthens the case for Lp(a) as a causal determinant of human longevity.…”
Section: Discussionmentioning
confidence: 54%
“…The increasing number of analyzed genomes of the elderly, in particular, centenarians, provides insights into the genetic predisposition of exceptional longevity. [ 94–96 ] Heritability of longevity (survival beyond the oldest percentiles) increases sharply with survival beyond the age of 90, [ 97 ] suggesting the existence of specific genes variants that centenarians share. [ 98 ] However, only the APOE (apolipoprotein E protein), FOXO3 (stress‐induced transcription factor forkhead box O3), and 5q33.3 (longevity locus on chromosome 5q33.3) loci are consistently associated with longer life span across studies.…”
Section: Omics‐based Molecule‐pattern Biomarkersmentioning
confidence: 99%
“…A recently performed GWAS in a relatively large human cohort ( n = 300 447) found 12 candidate loci associated with health span. [ 96 ] Among them, three single nucleotide polymorphism located at or near CDKN2B (cyclin‐dependent kinase inhibitor), LPA (apolipoprotein A), and HLA‐DQA1 (leucocyte antigen DQA1) losi were identified which were previously reported to be also associated with the longevity phenotype. [ 95,102 ] Surprisingly, however, gene variants of APOE were not revealed.…”
Section: Omics‐based Molecule‐pattern Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation